2013
DOI: 10.1093/gerona/glt133
|View full text |Cite
|
Sign up to set email alerts
|

Expression of DNA Methyltransferases Is Influenced by Growth Hormone in the Long-Living Ames Dwarf Mouse In Vivo and In Vitro

Abstract: Methyltransferase expression and DNA methylation are linked to aging and age-related disease. We utilized 3-, 12-, and 24-month-old Ames dwarf and their wild-type siblings to examine the genotype and age-related differences in the expression of methyltransferase enzymes related to DNA methylation in the liver, glycine-N-methyltransferase and DNA methyltransferase (DNMT). We found that DNMT proteins and transcripts are differentially expressed in dwarf mice compared with wild-type siblings that can be attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 62 publications
3
29
0
Order By: Relevance
“…For example, DNA methylation shows age‐specific linear changes in humpback whales ( Megaptera novaeangliae : Polanowski, Robbins, Chandler, & Jarman, 2014) but no changes in superb starlings (Rubenstein et al., 2016), possibly because these studies selected different candidate genes. In black grouse, we found a nonlinear (inverse u‐shaped) pattern of DNA methylation with age, as has similarly been reported in occasional human studies (for an example, see Armstrong, Rakoczy, Rojanathammanee, & Brown‐Borg, 2013). As our study focused primarily on the correlation between DNA methylation and sexual trait expression, such a pattern is to be expected.…”
Section: Discussionsupporting
confidence: 86%
“…For example, DNA methylation shows age‐specific linear changes in humpback whales ( Megaptera novaeangliae : Polanowski, Robbins, Chandler, & Jarman, 2014) but no changes in superb starlings (Rubenstein et al., 2016), possibly because these studies selected different candidate genes. In black grouse, we found a nonlinear (inverse u‐shaped) pattern of DNA methylation with age, as has similarly been reported in occasional human studies (for an example, see Armstrong, Rakoczy, Rojanathammanee, & Brown‐Borg, 2013). As our study focused primarily on the correlation between DNA methylation and sexual trait expression, such a pattern is to be expected.…”
Section: Discussionsupporting
confidence: 86%
“…We selected liver for this study because our previous studies showed differences in liver in expression of DNA methyltransferases (DNMTs) between WT and Ames mice and young and old mice [45]. Also, a single cell type, the hepatocyte, comprises ~80% of liver mass, and the epigenome of mouse liver has been extensively characterised, thereby aiding downstream analysis of the methylome in the context of the wider epigenetic landscape.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed methylation‐related pathways enriched in gene bodies gaining methylation. Interestingly, a previous study showed decreased expression of DNMT1 (Ray et al., 2006) in mouse T cells during aging; this is the main DNMT expressed in adulthood that maintains DNA methylation of adult dividing cells (Armstrong, Rakoczy, Rojanathammanee, & Brown‐Borg, 2014). These changes may contribute to misregulation of methylation machinery and a consequent entropy increase during aging.…”
Section: Discussionmentioning
confidence: 99%